Consumers' acceptance and preferance towards Heterotrigona spp. honey based on sensory characteristics - Saludin, Siti Farhana; Kamarulzaman, Nitty Hirawaty (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents an investigation of consumers’ acceptance and preference towards Heterotrigona spp. honey based on sensory characteristics. Heterotrigona spp. is a small stingless bee and due to their small size, this has made them easily to get honey from tiny and small flowers. As they can get honey from variety sources, the honey produced by Heterotrigona spp. has a very unique taste. This honey also has many benefits as it was proven can reduce cancer. There are several sensory characteristics associated with honey and based on these characteristics, researchers could identify and determine which sensory characteristics that mostly preferred by consumers.